Perbandingan Hasil Belajar Aquatik Antara Siswi Mts Dan Smp Di Kecamatan Cicalengka Dan Cikancung Kabupaten Bandung - Yulianti, Imas Ratna (2014)
Berdasarkan studi pendahuluan, didugaadanyaperbedaankarakteristikpembelajaranaktivitasaquatikantarasiswi yang bersekolah di sekolahumumdansekolah yang berlandaskankeagamaansehinggamembuatpenelititertarikuntukmengungkappembelajaranaquatik di keduasekolah yang berbedatersebut. Penelitianinidilakukan di SMPN 1 CicalengkadanMTsNCikancung.Pemilihansekolahinidilakuandenganteknikpurposive sampling. Data penelitiandiperolehdengancara test renanggayabebassecaralangsungdanpenilaiandenganmenggunakanlembarobservasi. Data yang telahdidapatkemudiandiolahdandianalisisdenganmenggunakanujistatistikparametrikujinormalitasLiliefors, ujihomogenitas, danujiduapihakuntukmengujihipotesis. Kesimpulandaripenelitiannilai rata-rata pada test akhir yang dilakukansiswi yang bersekolah di SMPN 1 Cicalengkasebesar 8,250. Sedangkannilai rata-rata yang dapatdiperoleholehsiswi yang bersekolah di MTsNCikancunghanyasebesar 4,550.Makadapatdisimpulkanbahwaterdapatperbedaanhasilbelajaraquatik (renanggayabebas) antarasiswi SMPN 1 Cicalengkadangansiswi MTsNCikancung. Kata kunci: hasilbelajar aquatic, renanggayabebas Based on the review study, suspected of the differences learning characteristic aquatic activity between the students who attended in public school and religious-school based on, that make the researcher interested in to reveal aquatic learning in the two different schools. This research was conducted at SMPN1Cicalengka and MTsNCikancung. The school selection was done by purposive sampling technique. The data were collected by freestyle swimming test directly and assessment using observation sheet. The data has been obtained and then processed and analyzed using parametric statistical test, Liliefors normality test, homogeneity test, and test the two parts to test the hypothesis. The conclusion of this study the average value at the end of the test, conducted on students who attend in SMPN 1 Cicalengka of 8,250. While the average value that can be obtained by students who attend in MTsNCikancung only 4,550. It can be conclude that there are differences in the result of aquatic learning (freestyle swimming) between students of SMPN 1 Cicalengka with students of MTsNCikancung. Keywords: Aquatic Activty, Freestyle Swimming,